The Perbedaan Keragaman Pangan dan Status Gizi Santri di Asrama dan Rumah Selama Pandemi COVID-19 : Individual Dietary Diversity Score and Nutritional Status Differerences among Islamic Boarding School Students Living at Dormitory and Home During COVID-19’s Pandemic - Lia Awwalia Majida; Martha Irene Kartasurya; Sri Achadi Nugraheni; Ani Margawati; Etika Ratna Noer (Universitas Airlangga, 2023)
Background: High school students at Islamic Boarding Schools (IBS) are continuing their learning activities at school during the COVID-19 pandemic, with the option to live either at home or in the dormitory. These differing living conditions may have an impact on individual dietary diversity scores (IDDS) and nutritional status. Objectives: To compare the IDDS and nutritional status of IBS students between dormitory living and home living during the COVID-19 pandemic. Methods: This study was conducted using a cross-sectional design involving 232 boys and girls (116 residing in the dormitory and 116 residing at home) aged 16-18 years, from 8 IBS located in Mranggen District, Demak Regency. The subjects were selected through systematic random sampling, adhering to specific inclusion and exclusion criteria. Data was collected using structured questionnaires that included IDDS, weight, and height measurements to calculate BMI Z-scores. Data were analyzed using Independent T, Mann Whitney U, Chi-Square, Rank Spearman Tests, and General Linear Models. Results: The subjects living at home consume a higher number (≥ 6) of food groups compared to those living in the dormitory. The malnutrition rates in dormitories are higher (40.5%). There were no significant differences in age and the number of confirmed COVID-19 cases between the two groups. The mean IDDS (5.4, p<0.001) and BMI Z-scores (0.26, p<0.001) of subjects living at home were higher than those living in the dormitory (3.7 and -0.73, respectively). The mean allowance for subjects living at home (Rp 325,948.3, p<0.001) was also higher than for those living in the dormitory (Rp. 224,913.8). Even after controlling for IDDS and allowance, the BMI Z-scores of subjects living at home remained higher than those in the dormitory. Conclusions: During the COVID-19 pandemic, IBS students who lived at home had higher food diversity and BMI Z-scores compared to those who lived in the dormitory. acceptability value and increased nutritional content compared to the control formula.